2021
DOI: 10.3390/nu13114038
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Its Association with the Level of Physical Activity in Fitness Center Users: Croatian-Based Study

Abstract: The Mediterranean diet (MD) is based on the traditional cuisine of south European countries, and it is considered one of the healthiest dietary patterns worldwide. The promotion of combined MD and physical activity has shown major benefits. However, the association between physical activity and the MD in regular fitness center users is still insufficiently investigated. This cross-sectional survey-based study was conducted on 1220 fitness center users in Croatia. The survey consisted of three parts: general in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
3
3
0
1
Order By: Relevance
“…In other words, all our participants with a higher total MET min/week score are more adherent to the MD, which is also in line with other studies that found a significant association between physical activity and adherence to the MD [6,41,42]. Our previous Croatia-based study conducted on recreational fitness center users showed a significant association between physical activity and adherence to the MD [6]. Moreover, after dividing our sample into tertiles based on the IPAQ-SF score, it was determined that the third tertile (MET > 3150 min/week) had the most fitness center users (34.4%) which were adherent to the MD, while the first tertile (MET < 1750 min/week) had the least (6.1%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other words, all our participants with a higher total MET min/week score are more adherent to the MD, which is also in line with other studies that found a significant association between physical activity and adherence to the MD [6,41,42]. Our previous Croatia-based study conducted on recreational fitness center users showed a significant association between physical activity and adherence to the MD [6]. Moreover, after dividing our sample into tertiles based on the IPAQ-SF score, it was determined that the third tertile (MET > 3150 min/week) had the most fitness center users (34.4%) which were adherent to the MD, while the first tertile (MET < 1750 min/week) had the least (6.1%).…”
Section: Discussionsupporting
confidence: 93%
“…Another important finding in our study is the significant positive correlation between physical activity and the MD. In other words, all our participants with a higher total MET min/week score are more adherent to the MD, which is also in line with other studies that found a significant association between physical activity and adherence to the MD [6,41,42]. Our previous Croatia-based study conducted on recreational fitness center users showed a significant association between physical activity and adherence to the MD [6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association between PA and adherence to the MD was also investigated in 1220 fitness-center users in Croatia [11]. Results showed that MD adherence, measured by means of the Mediterranean Diet Serving Score (MDSS) in the whole study sample (mean age was 29.1 ± 8.8 years) was 8.0, and 18.6% of participants adhered to the MD (total MDSS score ≥ 14).…”
mentioning
confidence: 99%
“…Ergül ve Sağlam [100] tarafından yapılan bir araştırmada, kalsiyum ve D vitamini suplementi kullanan kadınların IPAQ-SF puanları, kullanmayanlardan daha yüksek bulunmuştur. Martinovic ve arkadaşları [66] tarafından yapılan bir araştırmada, IPAQ-SF puanı en düşük olan bireylerin besin desteği kullanım oranlarının, puanı daha yüksek olan bireylerden daha düşük olduğu gösterilmiştir. Besin desteği kullanım oranları arasındaki farkın besin desteği çeşidine göre değiştiği de vurgulanmıştır.…”
Section: Uluslararası Fiziksel Aktivite Anketi-kısa Form (Ipaq-sf)unclassified